A review of inorganic particles synthesized through electrical discharge in different dielectric media: from devices, structures and components to applications - Liu, Yifan; Qin, Guilu; Yin, Liangjun; Jian, Xian; Li, Xianglong (Frontiers of materials science, 2024)
Size effects and compositions constitute new properties for inorganic particles in different application fields. The physical method has recently attracted more attention in the preparation of inorganic materials. Herein, a low-cost, eco-friendly, simple-operating, and time-saving technique, named electrical discharge, is reviewed in relation to developments from the nature of this technique in different dielectric media to the practical experience in controlling the main processing parameters, apparatuses, types of discharge, from the various structures and components to the wide applications. The development of the electrical discharge technique will play an important role in improving the technology to prepare superfine inorganic particles with high purity. Meanwhile, electrical discharge contributes to easily mixing solid materials from the atomic scale to several micrometers with different structures. Moreover, metal oxides or doping materials are accessible as the dielectric medium is changed. Considering some excellent advantages, new inorganic particles exploited through the electrical discharge method will promise to be the most rewarding in some potential applications.